Complications after Laparoscopic Appendectomy for Complicated Appendicitis - Nikolovski, Andrej; Tahir, Shenol; Mladenovikj, Dragoslav (Lietuvos chirurgija, 2020)
Background. Laparoscopic appendectomy is established method in the treatment of complicated appendicitis. Certain advantages of the technique do not fulfill the expectations for its superiority over the open appendectomy as when it is used for uncomplicated appendicitis. This is generally caused because of the high variety of postoperative complications reported in different series for complicated appendicitis. Material and methods. This prospective interventional clinical study analyzes 61 patients operated with laparoscopic and open appendectomy due to complicated appendicitis, with an end point of comparing the intra and postoperative complications in both groups. Results. Conversion in open appendectomy was forced in one patient (1.63%). The operative time was significantly shorter in the laparoscopic group (p = 0.048). Wound infection was significantly predominant in the open group (p = 0.045). Postoperative intraabdominal abscess occurred in one patient in the laparoscopic group (p = 0.52). The overall morbidity was 26.2% (7 patients in the laparoscopic, and 9 in the open group; p = 0.59). Length of stay was significantly shorter in the laparoscopic group (p = 0.00001). Conclusion. Certain significant advantages of the laparoscopic appendectomy as low incidence of wound infection, short hospitalization, less postoperative pain and faster socialization makes the laparoscopy up to date method in the treatment of complicated appendicitis.